Enhanced expression of nicotinamide nucleotide transhydrogenase (NNT) and its role in a human T cell line continuously exposed to asbestos - Shoko Yamamoto; Suni Lee; Hidenori Matsuzaki; Naoko Kumagai-Takei; Kei Yoshitome; Nagisa Sada; Yurika Shimizu; Tastsuo Ito; Yasumitsu Nishimura; Takemi Otsuki (Environment International, 2020)
The effects of asbestos fibers on human immune cells have not been well documented. We have developed a continuously exposed cell line model using the human T-lymphotropic virus 1 (HTLV-1)-immortalized human T cell line MT-2. Sublines continuously exposed to chrysotile (CH) or crocidolite (CR) showed acquired resistance to asbestos-induced apoptosis following transient and high-dose re-exposure with fibers. These sublines in addition to other immune cells such as natural killer cells or cytotoxic T lymphocytes exposed to asbestos showed a reduction in anti-tumor immunity. In this study, the expression of genes and molecules related to antioxidative stress was examined. Furthermore, complexes related to oxidative phosphorylation were investigated since the production of reactive oxygen species (ROS) is important when considering the effects of asbestos in carcinogenesis and the mechanisms involved in resistance to asbestos-induced apoptosis. In sublines continuously exposed to CH or CR, the expression of thioredoxin decreased. Interestingly, nicotinamide nucleotide transhydrogenase (NNT) expression was markedly enhanced. Thus, knockdown of NNT was then performed. Although the knockdown clones did not show any changes in proliferation or occurrence of apoptosis, these clones showed recovery of ROS production with returning NADPH/NADP+ ratio that increased with decreased production of ROS in continuously exposed sublines. These results indicated that NNT is a key factor in preventing ROS-induced cytotoxicity in T cells continuously exposed to asbestos. Considering that these sublines showed a reduction in anti-tumor immunity, modification of NNT may contribute to recovery of the anti-tumor effects in asbestos-exposed T cells. Keywords: Asbestos, T cell, Continuous exposure, Oxidative phosphorylation, nicotinamide nucleotide transhydrogenase (NNT)